2016
DOI: 10.1213/ane.0000000000001059
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiologist- and System-Related Risk Factors for Risk-Adjusted Pediatric Anesthesia-Related Cardiac Arrest

Abstract: Case-mix explained most associations between higher risk of pediatric ARCA and anesthesiologist-related variables at our institution, but the association with fewer annual days delivering anesthetics remained. Our findings highlight the need for rigorous adjustment for patient risk factors in anesthesia patient safety studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 25 publications
1
51
0
3
Order By: Relevance
“…The main strength of APRICOT is the detailed prospective capture of paediatric perioperative care and outcome data, including severe critical events and their treatment, in a large number of European centres . This revealed a high incidence of severe critical events but similar ultimate outcomes to previous reports . There was considerable variation across Europe in the incidence and management of severe perioperative critical events which has raised concerns about paediatric anaesthesia training, experience of teams in managing sick children, resources, and infrastructure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main strength of APRICOT is the detailed prospective capture of paediatric perioperative care and outcome data, including severe critical events and their treatment, in a large number of European centres . This revealed a high incidence of severe critical events but similar ultimate outcomes to previous reports . There was considerable variation across Europe in the incidence and management of severe perioperative critical events which has raised concerns about paediatric anaesthesia training, experience of teams in managing sick children, resources, and infrastructure .…”
Section: Discussionmentioning
confidence: 99%
“…Another strength of APRICOT was the use of detailed standardized definitions of the various serious critical events in paediatric anaesthesia. This could form the basis of a reporting and quality improvement system in Europe as has been developed in the USA . Currently, paediatric anaesthesia is not recognised as a subspecialty anywhere in Europe and training programs often do not allow acquisition of sufficient skills and experience to support independent practice .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to differing from adults, outcomes within pediatric practice may require consideration of specific age‐based subpopulations. In adults, ischemic heart disease and myocardial infarction are important cardiovascular outcomes, whereas congenital heart disease influences mortality, risk of perioperative cardiac arrest, and potential clinical indicators such as unplanned intensive care admission in children. Readmission is a core clinical indicator, but reasons for rehospitalization after discharge also differ between adults and children…”
Section: The Need For Core Outcome Sets For Pediatric Perioperative Carementioning
confidence: 99%
“…Demand for anesthesia services provided at off‐site locations (outside the traditional operating room) has increased over time and can consume a significant amount of resources at many institutions . Anesthesia provided in a traditional operating room has become remarkably safe, with the incidence of significant perioperative events such as cardiac arrest or anesthesia‐related mortality in children reported to be 5.3‐8.5 per 10 000 and 0.18‐0.36 per 10 000 anesthetics, respectively . Studies of adverse events (AEs) in off‐site locations have typically been retrospective in nature and involve mainly non‐anesthesia sedation providers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Anesthesia provided in a traditional operating room has become remarkably safe, with the incidence of significant perioperative events such as cardiac arrest or anesthesia-related mortality in children reported to be 5.3-8.5 per 10 000 and 0.18-0.36 per 10 000 anesthetics, respectively. [4][5][6] Studies of adverse events (AEs) in offsite locations have typically been retrospective in nature and involve mainly non-anesthesia sedation providers. Kakavouli et al showed no difference in the incidence of AE in off-site compared to operating room locations when care was provided by anesthesia providers 7 and Vlassakova et al reviewed a single institution's experience with STAT calls (calls for help), finding significantly fewer calls in remote locations compared to traditional ORs.…”
Section: Introductionmentioning
confidence: 99%